2002
DOI: 10.1038/sj.jhh.1001408
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria is an integrated marker of subclinical organ damage in primary hypertension

Abstract: Increased urine albumin excretion is associated with an unfavourable cardiovascular risk profile and prognosis in primary hypertension, even though its pathogenesis is currently unknown. Microalbuminuria (Mi) has been proposed as an integrated marker to identify patients with subclinical organ damage, but its routine use is still too often neglected in clinical practice. The aim of our study was to evaluate the relationship between urinary albumin excretion and early signs of subclinical target organ damage (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 27 publications
2
47
0
Order By: Relevance
“…What is even more important, microalbuminuria is a highly specific predictor of the simultaneous occurrence of both cardiac and vascular abnormalities. In a group of 346 patients with essential hypertension, we observed that patients with microalbuminuria actually show an almost 20-fold greater risk for having both left ventricular hypertrophy and carotid wall abnormalities (8). In light of these observations, it is not surprising that microalbuminuria was found to be an excellent predictor of cardiovascular morbidity and mortality in hypertensive patients in several prospective studies (9).…”
Section: Microalbuminuria As An Integrated Marker Of Cardiovascular Riskmentioning
confidence: 91%
“…What is even more important, microalbuminuria is a highly specific predictor of the simultaneous occurrence of both cardiac and vascular abnormalities. In a group of 346 patients with essential hypertension, we observed that patients with microalbuminuria actually show an almost 20-fold greater risk for having both left ventricular hypertrophy and carotid wall abnormalities (8). In light of these observations, it is not surprising that microalbuminuria was found to be an excellent predictor of cardiovascular morbidity and mortality in hypertensive patients in several prospective studies (9).…”
Section: Microalbuminuria As An Integrated Marker Of Cardiovascular Riskmentioning
confidence: 91%
“…This finding can be explained that electrocardiographic change due to LVH and BP control might occur more easily than an echocardiographic left ventricular mass change. MAU is known to be the integrated marker of SODs in primary hypertension [15]. MAU is associated with metabolic derangements and an increased cardiovascular risk in hypertension patients [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…All these factors may have contributed to the hypothesis that echocardiographic left ventricular hypertrophy has a much smaller impact on risk stratification according to the 2003 guidelines. 7,8 Microalbuminuria has been shown to be correlated with left ventricular mass, 12,23,24 and might therefore have lowered the independent value of echocardiography to detect target organ damage. These findings may also be seen as an indirect confirmation of the integrative role of microalbuminuria in the development and progression of cardiovascular disease in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%